Trois revues féministes italiennes : DonnaWomanFemme (DWF), Via Dogana, Leggendaria (années 1970-2000) - Nadia Setti (Laboratoire Italien)
This paper traces the history, main themes and goals of three important Italian feminist magazines DonnaWomanFemme (DWF) (1975 to present), Via Dogana (1991-2014) and Leggendaria (1997 to present). Each of these magazines is an essential document which explains the evolution of and changes in Italian feminism, the emergence and circulation of ideas, practices and feminist theories from the 1970s to the present day, and their cultural, social, and political impact, in a national and international perspective. The analysis of these publications is structured around five thematic axes: feminist politics; feminist archives, bookshops and libraries; work, insecurity, care; body, sexuality, gender; writing, literature, literary criticism, languages.